1995
DOI: 10.1016/0014-5793(94)01336-y
|View full text |Cite
|
Sign up to set email alerts
|

A 70 kDa protein is transferred from the outer acrsomal to the plasma membrane during capacitation

Abstract: Bull sperm plasma and outer acrosomal membranes were analyzed by SDS-PAGE. Analysis of the plasma membrane proteins revealed the presence of a 70 kDa band the prominence of which is enhanced after capacitation. This protein was found to bind to zona pellucida intact oocytes. PAGE analysis of outer acrosomal membrane proteins also reveals the presence of a 70 kDa band, but its prominence decreases after capacitation. This protein also binds to zona pellucida intact oocytes. Futhermore, the 70 kDa outer acrosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
(48 reference statements)
2
15
0
Order By: Relevance
“…ARHGAP6 has two independent functions as follows: a specific GAP for RhoA, and a promoter of actin remodeling (45). As RhoA is implicated in cell motility (55,56) and actin remodeling is implicated in hyperactivated motility and the acrosome reaction (46,47), phosphorylation of sperm ARHGAP6 by ERK may be involved in sperm motility, capacitation, and acrosome reaction via RhoA. Other potential substrates are the dyneins, the sperm motor molecules of the axoneme (48), known to be phosphorylated during activation (49).…”
Section: Discussionmentioning
confidence: 99%
“…ARHGAP6 has two independent functions as follows: a specific GAP for RhoA, and a promoter of actin remodeling (45). As RhoA is implicated in cell motility (55,56) and actin remodeling is implicated in hyperactivated motility and the acrosome reaction (46,47), phosphorylation of sperm ARHGAP6 by ERK may be involved in sperm motility, capacitation, and acrosome reaction via RhoA. Other potential substrates are the dyneins, the sperm motor molecules of the axoneme (48), known to be phosphorylated during activation (49).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that actin polymerization during sperm capacitation depends on phospholipase D activity, which is regulated by the cross-talk between PKA and protein kinase C (PKC) (1,28). Moreover, we showed elsewhere that PIP 2 (4,5) , the cofactor for phospholipase D activation and F-actin production during sperm capacitation, is mediated by phospha-tidylinositol 4-kinase (PI4K) but not by phosphatidylinositol 3-kinase (PI3K) activity (29).…”
mentioning
confidence: 92%
“…Another important process that occurs during sperm capacitation is actin polymerization; however, at the end of the capacitation, the polymers must disperse to achieve the AR (3). It has been suggested that an increase in F-actin creates a network between the plasma and the outer acrosomal membranes, and the dispersion of F-actin between the two membranes is needed to enable the AR (3)(4)(5)(6).…”
mentioning
confidence: 99%
See 2 more Smart Citations